Phylogeny of the tribe Erotini (Coleoptera, Lycidae), with descriptions of new taxa - Kazantsev, Sergey V. (Zootaxa, 2004)
A cladistic analysis of Erotini (Lycidae) is carried out, resulting in revalidation of Dictyopterini nom. rev., proposal of Aferotini tr. n. and Flagraxina subtr. n. The genera Proteros gen. n. and Pyrotes gen. n. and eight new species: Proteros sempiternus sp. n., Taphomimus nanensis sp. n., Dictyoptera gansuensis sp. n., Helcophorus murzini sp. n., H. gobindanus sp. n., Greenarus belokobylskii sp. n., Eropterus glebulus sp. n. and Propyropterus (s. str.) plateroides sp. n. are described. Benibotarus sanguinipennis Nakane, syn. n. is placed in synonymy with Laterialis oculata (Gorham). Lycoprogentes Pic is transferred from Calochrominae to Taphini (Erotinae) and Microcoloberos Pic is transferred from Erotinae to Platerodinae. Erotides Waterhouse nom. rev. and Glabroplatyis Pic nom. rev. are revalidated from synonymy with Platycis Thomson. Punicealis miranda (Barovskij) nom. rev. is revalidated from synonymy with Laterialis oculata (Gorham). Platycis sculptilis (Say) is transferred to Erotides (s. str.), while Platycis cosnardi (Chevrolat), P. nasuta (Kiesenwetter), P. schneideri (Kiesenwetter), P. taiwana Kono, P. kanoi Nakane and P. matsudai Boc k are transferred to Erotides (Glabroplatycis); Benibotarus nigripennis Nakane & Ohbayashi is transferred to Greenarus Kazantsev and Pyropterus himalejicus Bourgeois to Lycoprogentes. Helcophorus Fairmaire, stat. n., Taphomimus Kazantsev, stat. n., Punicealis Kazantsev, stat. n., Laterialis Kazantsev, stat. n., and Greenarus Kazantsev, stat. n. are raised to the genus level, while Paralopheros Kazantsev is suppressed to subgeneric level within Propyropterus Nakane. The subgenus Tricostaeptera Kazantsev is transferred from Kolibaceum to Laterialis. Kleineria nom. n. is proposed for Kleinella Kazantsev, 1992 preoccupied by Kleinella Adams, 1860 (Mollusca). A key to the genera and subgenera and a check-list of Erotini and Dictyopterini of the World are provided.